2017
DOI: 10.7717/peerj.3324
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of false-positive observations in botanical surveys

Abstract: Errors in botanical surveying are a common problem. The presence of a species is easily overlooked, leading to false-absences; while misidentifications and other mistakes lead to false-positive observations. While it is common knowledge that these errors occur, there are few data that can be used to quantify and describe these errors. Here we characterise false-positive errors for a controlled set of surveys conducted as part of a field identification test of botanical skill. Surveys were conducted at sites wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For instance, Farmer et al ( 2012 ) found a tendency for more false positives of rare species to be recorded by participants with higher expertise. In contrast, Groom and Whild ( 2017 ) found false positives to be uniformly distributed among observers of different expertise, yet both studies reported higher frequencies of false positive detections for rarer species when compared to more common species. Increasing participants’ observational skills, in the aim of reducing false negative and false positive detections, may be directly addressed by providing training and feedback (but see Feldman et al 2018 ), although such an option is often not feasible for many community science projects.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, Farmer et al ( 2012 ) found a tendency for more false positives of rare species to be recorded by participants with higher expertise. In contrast, Groom and Whild ( 2017 ) found false positives to be uniformly distributed among observers of different expertise, yet both studies reported higher frequencies of false positive detections for rarer species when compared to more common species. Increasing participants’ observational skills, in the aim of reducing false negative and false positive detections, may be directly addressed by providing training and feedback (but see Feldman et al 2018 ), although such an option is often not feasible for many community science projects.…”
Section: Introductionmentioning
confidence: 88%
“…The reason is that false positives cannot be distinguished from true positives from reported detections alone. However, false positives are common in community science data, particularly for studies that aim at detecting recently introduced and hence rare alien species that are therefore easily misidentified (Groom and Whild 2017 ). To learn false positive rates in an occupancy setting, additional information must be available, either in the form of ground-truth at a subset of locations, or confirmed detections (e.g., by requesting to upload pictures of the observed individual(s) (Chambert et al 2015 ; Vantieghem et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, I have focussed simply on the probability that an individual organism will be detected by an observer if it is available to be detected. In the context of estimating occurrences and abundances it is important not just if an individual that is present is not detected (a false negative) but also if an individual is detected when it is not actually there (a false positive), and the frequency with which these errors occur has been a focus of some research attention (Groom & Whild, 2017; Miller et al., 2012). One might argue that while false negatives reduce human–nature interactions, false positives matter a good deal less, as there may nevertheless be benefits to be obtained by a person from positive human–nature interactions that did not actually occur but which they perceived to do so (although this would obviously not extend to false‐positive interactions with species that cause undue anxiety).…”
Section: Probability Of Detection Given Availability (Pd)mentioning
confidence: 99%
“…This might be a property of the spatial distribution of rare species, but it may also reflect an over-sampling of rare species. For example, if observers are more interested in observing and recording rare species than common ones or if rare species are more likely to be false-positive observations (Groom & Whild, 2017). Biogeographic atlas data are rarely, if ever, a completely systematic sample and often contain spatial and taxonomic sampling biases (Dennis & Thomas, 2000;Rich & Woodruff, 1992).…”
Section: Suitable Use Casesmentioning
confidence: 99%